Human behavior and sustainability. Issue 3 (27th February 2012) - Fischer, Joern; Dyball, Robert; Fazey, Ioan; Gross, Catherine; Dovers, Stephen; Ehrlich, Paul R; Brulle, Robert J; Christensen, Carleton; Borden, Richard J
Abstract : Sustainability demands changes in human behavior. To this end, priority areas include reforming formal institutions, strengthening the institutions of civil society, improving citizen engagement, curbing consumption and population growth, addressing social justice issues, and reflecting on value and belief systems. We review existing knowledge across these areas and conclude that the global sustainability deficit is not primarily the result of a lack of academic knowledge. Rather, unsustainable behaviors result from a vicious cycle, where traditional market and state institutions reinforce disincentives for more sustainable behaviors while, at the same time, the institutions of civil society lack momentum to effectively promote fundamental reforms of those institutions. Achieving more sustainable behaviors requires this cycle to be broken. We call on readers to contribute to social change through involvement in initiatives like the Ecological Society of America's Earth Stewardship Initiative or the nascent Millennium Alliance for Humanity & the Biosphere .